PET/CT in malignant melanoma: a two‐tiered healthcare system? Updated healthcare situation regarding initial staging of malignant melanoma with PET/CT. (22nd April 2021) - Matiszick, Antonia; Völker, Charlyn; Garbe, Claus; Gutzmer, Ralf; Forschner, Andrea; Wagner, Gunnar; Franzius, Christiane; Czech, Norbert; Schüssler, Frank; Meier, Friedegund; Sachse, Michael Max
Summary: Background: Patients with stage IIC malignant melanoma are recommended to undergo cross‐sectional imaging for initial staging. PET/CT is superior to other methods regarding its diagnostic accuracy of the tumor spread in stage III. So far there is no meaningful data on the nationwide availability, usage and cost recovery of this imaging technique. Patients and methods: Questionnaires on the healthcare situation in 2018 were sent to all German dermatology clinics and PET/CT centers in March and April 2019. Results: 61.2 % of the dermatology clinics (71/115) and 48.2 % of the PET/CT centers (77/160) took part in the survey. A total of 22, 645 patients with malignant melanoma were seen in these clinics in 2018. 16.8 % of the patients with stage IIC melanoma received a PET/CT for primary staging. The costs of this examination were covered for all statutory and privately insured patients in 40 % and 68 % of dermatology clinics (20/50 and 34/50), respectively. 68.0 % (34/50) of all dermatology clinics reported relevant changes of treatment according to PET/CT findings. Long examination periods by the health insurance companies and the time required to submit the application were the most common reasons for dermatology clinics to reject a request for PET/CT. Relevant incidental findings were reported in 90.2 % (47/51) of all PET/CT centers. Conclusions: There are clear differences in the nationwide availability and cost coverage of PET/CT in primary staging for stage IIC melanoma. For these reasons, a two‐tiered healthcare system may be assumed.